2013
DOI: 10.1158/1538-7445.am2013-4117
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4117: Defective quorum sensing in Ph+ ALL and identification of diffusible factors secreted by cells growing at high cell density.

Abstract: Quorum sensing (QS) is a generic term describing cell-cell communication and collective decision making by bacteria and social insects to regulate expression of specific genes controlling cell density and other properties in response to changes in nutrient supply or environment. QS also has a role in higher organisms in maintaining homeostasis, regulation of the immune system and behavior of cancer cell populations. CML is a classic example of a tumor which without effective therapy consistently undergoes mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A newly established cell line freshly obtained from the leukemic cells growing as ascitic cells in the pleural effusion of a terminally ill patient with Ph+ acute lymphoblastic leukemia (ALL3) is used in this work. ALL3 is a clonal proliferation of p190 BCR-ABL transformed pre B cells that arise in the bone marrow [30,34]. We observed that there is a significant difference in the growth rate of ALL3 cells at low (LD) and high starting cell densities (HD).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…A newly established cell line freshly obtained from the leukemic cells growing as ascitic cells in the pleural effusion of a terminally ill patient with Ph+ acute lymphoblastic leukemia (ALL3) is used in this work. ALL3 is a clonal proliferation of p190 BCR-ABL transformed pre B cells that arise in the bone marrow [30,34]. We observed that there is a significant difference in the growth rate of ALL3 cells at low (LD) and high starting cell densities (HD).…”
Section: Introductionmentioning
confidence: 98%
“…However, the influence of cell-cell communication on biomechanical properties of cells has not been systematically studied. At the same time, it is known that the collective behavior is an important feature and it is involved in regulating many biological processes such as cell migration, stem cell maintenance, growth of proper organ size, immune system regulation, hematopoiesis, homeostasis and regeneration [27][28][29][30][31][32][33][34]. Individual cells utilize 'autocrine' and/or 'paracrine' factors to coordinate these beneficial collective behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations